Perencanaan Lapis Fondasi Daur Ulang Menggunakan Lapis Fondasi Atas dan Lapis Aspal Eksisting - Diyanti Diyanti; Andi Asnur Pranata; Ellysa Ellysa; Sri Indah Setiyaningsih (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The current technology for using recycled materials in road preservation work is very helpful in maintaining the sustainability of the materials used. Waste from road materials that will be repaired can be reused for new foundation layers. The aim of this research is to obtain a design for the percentage of cement, percentage of emulsified asphalt, unconfined compressive strength and optimum water content in accordance with the applicable engineering specifications so that it can be proven that the existing material from the top foundation layer and asphalt layer can still be used as a new foundation layer. The research method involves conducting experiments on existing materials by conducting laboratory tests on samples of top foundation layer aggregate and existing asphalt in the Cikarang Industrial Area. The experiment was carried out at the Jakarta State Polytechnic Civil Engineering Laboratory with 9 test samples. The results obtained for the recycled foundation layer were that the design cement required was 30.8 grams and 53.1 grams of emulsified asphalt for an area of ​​1m2 with a 7 day unconfined compressive strength obtained from nine samples for variations in cement content of 1%, 3%, and 5% maximum 2.81MPa, so the optimum cement content is 3.6%.